Effect of different CAD/CAM cutting depths on the post-fatigue load-bearing capacity of novel multilayer zirconia restorations. (August 2021) - Li, Xuejing; Wang, Qiang; Qiu, Xiaohai; Zhao, Baohong
Highlights: Restorations can be milled at various CAD/CAM cutting depths in a novel multilayer zirconia disk depending on the durability and esthetic requirements. Attenuation, due to fatigue, in the load-bearing capacity of zirconia restorations subjected to 10 6 cycles may be not detected. However, after a long-term service of 2 × 10 6, 3 × 10 6, or 4 × 10 6 cycles, fatigue degraded the load-bearing capacity of restorations considerably. The load-bearing capacity and fracture behavior of multilayer zirconia restorations were comparable to zirconia restorations with homogeneous structures. Abstract: Objectives: To investigate the post-fatigue load-bearing capacity of restorations milled at various cutting depths in a novel strength- and color-gradient multilayer zirconia CAD/CAM disk. Methods: Identical crowns were divided into 4 groups ( n  = 25 per group): crowns milled at 3 CAD/CAM cutting depths in multilayer zirconia disks as 3 experiment groups and homogeneous zirconia crowns as a control group. The color differences between various cutting depths were measured. In each group, crowns were tilted at 15° and subjected to fatigue loading for various numbers of cycles (0, 10 6, 2 × 10 6, 3 × 10 6 or 4 × 10 6, n  = 5 per subgroup). All surviving crowns were subsequently submitted to a static fracture test to determine load-bearing capacity. The data were analyzed by ANOVA and Weibull distribution analysis. Failure modes were observed with SEM. Results: For a novel multilayer zirconia, a deeper CAD/CAM cutting depth corresponded to a higher load-bearing capacity but a darker color. After 10 6 cycles of fatigue loading, there was not a significant reduction in fracture load. However, after 4 × 10 6 cycles, the load-bearing capacity of all crowns decreased significantly by approximately 50%. For multilayer and homogeneous zirconia materials, similar failure mode and Weibull modulus were identified. Conclusions: Restorations can be milled at various CAD/CAM cutting depths in a novel multilayer zirconia disk depending on the durability and esthetic requirements. The load-bearing capacity of multilayer restorations degraded significantly after 4 × 10 6 cycles of fatigue loading, but not after 10 6 cycles. Clinical Significance: For a novel multilayer zirconia disk, a posterior restoration can be milled from the middle or bottom of the disk to improve its load-bearing capacity. For an anterior restoration, to meet the esthetic requirements, milling the entire thickness of a multilayer disk is recommended. Graphical abstract: Image, graphical abstract